Binding of pleiotrophin to cell surface nucleolin mediates prostate cancer cell adhesion to osteoblasts. (June 2022) - Lamprou, Margarita; Koutsioumpa, Marina; Kaspiris, Angelos; Zompra, Katerina; Tselios, Theodoros; Papadimitriou, Evangelia
Abstract: Pleiotrophin (PTN) is a growth factor that appears to play an important role in prostate cancer growth and angiogenesis. We have previously shown that decreased PTN expression in human prostate cancer PC3 cells leads to decreased adhesion of prostate cancer cells to osteoblasts, suggesting that PTN mediates this interaction. In the current work, using peptides that correspond to different regions of the PTN protein, we identified that a domain responsible for the adhesion of prostate cancer cells to osteoblasts corresponds to amino acids 16–24 of the mature PTN protein. Given that a synthetic PTN16–24 peptide which disturbs the interaction of PTN with nucleolin (NCL) was found to inhibit prostate cancer cells' adhesion to osteoblasts, it seems that NCL mediates the cellular interactions involved in the adhesion process. Two pseudopeptides that bind to cell surface NCL and an anti-NCL antibody also decrease prostate cancer cell adhesion to osteoblasts to the same degree as PTN16–24, further supporting the involvement of cell surface NCL in this interaction. Collectively, our data suggest that NCL on the cell surface of osteoblasts may mediate adhesion of prostate cancer cells through PTN and identify peptides that could be exploited therapeutically to target this component of prostate cancer bone metastases. Highlights: Cell surface nucleolin in osteoblasts is the prostate cancer PTN binding molecule. The N-terminal TSR domain of PTN may mediate prostate cancer cell adhesion to osteoblasts. A synthetic PTN16-24 peptide inhibits PTN binding to nucleolin. PTN16-24 and cell surface nucleolin inhibitors decrease prostate cancer cell adhesion to osteoblasts. The identified peptides could be exploited to target prostate cancer bone metastases.